2014
DOI: 10.1155/2014/354648
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Minor Salivary Gland Biopsy for the Diagnosis of Amyloidosis in a Rheumatology Clinic

Abstract: Background. Systemic amyloidosis is a potentially fatal condition, unless diagnosed and treated before development of irreversible organ damage. Demonstration of amyloid deposits within tissue biopsies is only definitive diagnostic method, which makes appropriate selection of biopsy site essential. Herein, we evaluated efficacy of minimally invasive minor salivary gland biopsy (MSGB) for the diagnosis of amyloidosis. Methods. We analyzed 37 biopsies taken from 35 patients. Suggestive findings for amyloidosis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
0
12
0
2
Order By: Relevance
“…A kidney biopsy is recommended whenever the urinary protein excretion exceeds 0.5 g/24 h to exclude AA amyloidosis [140]. More convenient sites for the tissue biopsies are abdominal fat and minor salivary glands [141]. The other option for patients with suspected amyloidosis is the use of a serum amyloid P (SAP) scan but it is only available at certain centers [142].…”
Section: Follow-upmentioning
confidence: 99%
“…A kidney biopsy is recommended whenever the urinary protein excretion exceeds 0.5 g/24 h to exclude AA amyloidosis [140]. More convenient sites for the tissue biopsies are abdominal fat and minor salivary glands [141]. The other option for patients with suspected amyloidosis is the use of a serum amyloid P (SAP) scan but it is only available at certain centers [142].…”
Section: Follow-upmentioning
confidence: 99%
“…Notably, there was a strong predominance of female patients (83.76%) (Table S2). The average follow-up period after the biopsy presented large variation and included 1 month, 12,14,23,24 1 year 11,13,25,26 or even 2 years. [27][28][29] Four studies compared the lip biopsy with parotid gland biopsy.…”
Section: Re Sultsmentioning
confidence: 99%
“…Neurological complications were the most common postsurgical complication in 20 studies, followed by pain, [12][13][14][15][23][24][25]27,33 swelling, 12,13,22,23,27,33 and hematoma. 14,15,22,23,27 Three studies 9,28,37 reported no complications.…”
Section: Re Sultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Для биопсии пригодны также почка, кожа, желудок, слизистая оболочка прямой кишки, икроножный нерв, удерживатель сгибателей и околосухожильный жир, полученный после оперативного вмешательства по поводу кистевого туннельного синдрома, слюнная железа. Малоинвазивная биопсия слюнной железыбезопасный и простой метод выявления амилоидоза, который может быть выполнен в амбулаторных условиях без подготовки к процедуре, его чувствительность составляет 61% [28,29]. Чувствительность эндоскопической биопсии слизистой оболочки желудочно-кишечного тракта составляет 85%, в то время как биопсия икроножного нерва является менее чувствительной.…”
Section: обзорыunclassified